Exosomes as Reconfigurable Therapeutic Systems. Issue 7 (July 2017) - Conlan, R. Steven; Pisano, Simone; Oliveira, Marta I.; Ferrari, Mauro; Mendes Pinto, Inês
Abstract : Historically, small molecules, including steroid hormones and cytokines, have been attributed a role in paracrine and endocrine signaling, and now include a new player: biological nanoparticles, or 'exosomes'. Generated intracellularly, and defined simply as nanoparticulate packages of signaling moieties, exosomes have emerged as vehicles for highly specialized local and distant intercellular communication. Exosomes are increasingly being recognized as contributing factors in many diseases, and their potential as biomarkers and in therapeutics is rapidly emerging. This review highlights recent advances in the exploitation of exosomes in diagnostic and therapeutic applications. We discuss various facets of nanoparticles, namely the isolation and manipulation of exosomes, the construction of synthetic exosome-like particles in vivo, and their potential use in the treatment of various diseases. Trends: Exosome diagnostics, although available, remain unapproved by regulatory agencies, and thus might be used in parallel with existing approved tests. Exosome approaches to therapeutic interventions are far-reaching – from packaging of therapeutic agents to driving immune responses. Applications range from oncology to regenerative medicine, and commercial GMP production at therapeutically relevant quantities is underway. Exosomes can trigger positive and negative immunomodulatory effects, as observed in early exosome clinical trials for advanced non-small cell lung cancer, thus potentially impacting on disease progression. The effects of mesenchymal stem cell (MSC) delivery to patients showing therapeutic benefit appear to be exosome-derived because exosomes purified from MSCs can promote similar effects to MSC-based treatments. The potential for tumor-derived exosomes to control the establishment of organ-specific pre-metastatic niches has been demonstrated through their ability to program bone marrow-derived cells towards a pro-metastatic phenotype.